The Influence of the Media in Shaping Public Opinion and How Society Views It: Penelitian - Tahir; Hasan, Rahmat (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Mass media and social media have emerged as controlling powers over public perception of worldwide concerns, including the Israel-Palestine conflict. Within the reality of the Palestinian genocide, the media, aside from being a transmitter of information, also serves as a means of manipulating narratives. Language use, visualization of violence, and editorial leanings tend to impact people's perception of the conflict's reality. The issue provokes inquiry into media neutrality and the degree to which the public can discern fact from narrative constructions. This research was aimed at examining the way the media influenced international and national public opinion about Israel's military attack on Palestine, and the lack of balance in the representation of these events across different information media. The research was qualitative in nature, using critical discourse analysis of both mainstream media and social media reporting. The findings showed that framing of news stories substantially affected public sympathy or dislike for victims, which in turn had an impact on societal attitudes and even foreign political agendas (Hroub, 2022). This research stressed the need for media literacy as a social safeguard against information manipulation.